2004
DOI: 10.1038/sj.hdy.6800526
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and dominance of self-incompatibility alleles in polyploid Arabidopsis lyrata

Abstract: Natural populations of diploid Arabidopsis lyrata exhibit the sporophytic type of self-incompatibility system characteristic of Brassicaceae, in which complicated dominance interactions among alleles in the diploid parent determine selfrecognition phenotypes of both pollen and stigma. The purpose of this study was to investigate how polyploidy affects this already complex system. One tetraploid population (Arabidopsis lyrata ssp kawasakiana from Japan) showed complete self-compatibility and produced viable sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 68 publications
5
52
1
Order By: Relevance
“…From the banding patterns observed a hypothesis of the constituent SRK types was formed. Subsequently, the hypothesis was confirmed, using primers designed specifically for each SRK type (see also Mable et al 2003Mable et al , 2004 for this typing strategy and primer sequences). In each case, the procedure included negative controls (i.e., plants without the haplotype).…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…From the banding patterns observed a hypothesis of the constituent SRK types was formed. Subsequently, the hypothesis was confirmed, using primers designed specifically for each SRK type (see also Mable et al 2003Mable et al , 2004 for this typing strategy and primer sequences). In each case, the procedure included negative controls (i.e., plants without the haplotype).…”
Section: Methodsmentioning
confidence: 96%
“…Data analysis: The S-phenotype of an individual was inferred from the genotype and from the current understanding of dominance relations among the S-haplotypes (Schierup et al 2001;Mable et al 2003Mable et al , 2004. From the deduced phenotypes the proportion of compatible matings among the adult plants was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This assumption can be applied for diploid A. lyrata with its wellinvestigated sporophytic self-incompatibility system (e.g., ref. 37), which prevents self-pollination, and also for tetraploid A. lyrata, as Mable et al (17) demonstrated that the tetraploids from eastern Austria remained selfincompatible. The mating system of A. arenosa was addressed in a greenhouse experiment: Over a period of 3 y, we performed selfing and reciprocal outcrossing experiments with the populations that were studied with microsatellite markers.…”
Section: Methodsmentioning
confidence: 99%